China's Labor Market Demand in the Shadow of COVID-19: Evidence from an Online Job Board - Xiangquan Zeng; Shuai Chu; Xuan Chen (Global Labor Organization (GLO), 2022)
Using data of the largest online job board in China, Zhaopin.com, we examine the impacts of the lockdown policy on the Chinese labor market demand during the coronavirus disease (COVID-19) pandemic. The analyses reveal that the lockdown policy, which was implemented in Wuhan on January 23, 2020, reduced the labor market demand drastically. Specifically, the "Number of Companies" that posted weekly job vacancies, "Number of Positions," and "Number of Employees" to be recruited reduced rapidly by 18.5%, 21.9%, and 30.0%, respectively. Furthermore, this impact of the lockdown policy began to reduce, thus allowing the labor demand to rebound four weeks after the outbreak. The heterogeneity analyses reveal that the industries with high physical proximity and those manufacturing non-essential products/services, as well as small-size firms, were greatly impacted by the policy. No statistical difference was observed between the impacts on the cities that implemented specific control measures and those that did not. This study quantifies the dynamic impacts of China's stringent control measures on the country's labor demand during the pandemic. These findings indicate that the effective management of public health crises in conjunction with economic policies is critical to revitalizing labor markets.
Keywords: I18; H51; J23; 330; COVID-19; lockdown; job vacancy; online job board; labor demand